Letter: concordance of SVR4 and SVR12 following direct‐acting anti‐viral treatment in Egypt. Issue 11 (June 2018) - El Kassas, M.; Funk, A. L.; Abd El Latif, Y.; Vasiliu, A.; Sherief, A.; Shimakawa, Y.; Youssef, N.; El Tahan, A.; Elbadry, M.; Farid, A. M.; El Shazly, Y.; Doss, W.; et al.
Abstract : Linked Content This article is linked to Omar et al paper. To view this article visithttps://doi.org/10.1111/apt.14428 .